Analisis Pengaruh Variabel Makro Ekonomi Terhadap Prevalensi Stunting Di Indonesia - Viezani, Ezra Shafa; Yeni, Isra; Rahmizal, Maizul (Universitas Negeri Padang, 2024)
This study aims to analyze the influence of Poverty, Economic Growth Rate, Government Policy and Exclusive Breastfeeding on Stunting Prevalence in Indonesia. This study uses a panel data regression analysis method with a Random Effect Model (REM). The results of the study show that Poverty has a significant positive effect on Stunting Prevalence, and Government Policy and Exclusive Breastfeeding have a significant negative effect on Stunting Prevalence, and Economic Growth Rate has no effect on Stunting Prevalence in Indonesia.